Toxicokinetic/Toxicodynamic Interaction Studies in Rats between the Drugs of Abuse γ-Hydroxybutyric Acid and Ketamine and Treatment Strategies for Overdose - Nisha V. Kwatra; Marilyn E. Morris (MDPI AG, 2021)
γ-hydroxybutyric acid (GHB) is widely abused alone and in combination with other club drugs such as ketamine. GHB exhibits nonlinear toxicokinetics, characterized by saturable metabolism, saturable absorption and saturable renal reabsorption mediated by monocarboxylate transporters (MCTs). In this research, we characterized the effects of ketamine on GHB toxicokinetics/toxicodynamics (TK/TD) and evaluated the use of MCT inhibition and specific receptor antagonism as potential treatment strategies for GHB overdose in the presence of ketamine. Adult male Sprague-Dawley rats were administered GHB 600 mg/kg i.v. alone or with ketamine (6 mg/kg i.v. bolus plus 1 mg/kg/min i.v. infusion). Plasma and urine samples were collected and respiratory parameters (breathing frequency, tidal and minute volume) continuously monitored using whole-body plethysmography. Ketamine co-administration resulted in a significant decrease in GHB total and metabolic clearance, with renal clearance remaining unchanged. Ketamine prevented the compensatory increase in tidal volume produced by GHB, and this resulted in a significant decline in minute volume when compared to GHB alone. Sleep time and lethality were also increased after ketamine co-administration when compared to GHB. L-lactate and AR-C155858 (potent MCT inhibitor) treatment resulted in an increase in GHB renal and total clearance and improvement in respiratory depression. AR-C155858 administration also resulted in a significant decrease in GHB brain/plasma ratio. SCH50911 (GABAB receptor antagonist), but not naloxone, improved GHB-induced respiratory depression in the presence of ketamine. In conclusion, ketamine ingestion with GHB can result in significant TK/TD interactions. MCT inhibition and GABAB receptor antagonism can serve as potential treatment strategies for GHB overdose when it is co-ingested with ketamine.